PENGEMBANGAN TEKNOLOGI PEMBELAJARAN PAI BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN PEMAHAMAN MATERI KEAGAMAAN dI SEKOLAH - Umraniah, Umraniah; Acetylena, Sita (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
Islamic Religious Education (PAI) in schools faces challenges in delivering engaging content in the digital era. Augmented Reality (AR) emerges as a potential innovation to address this issue by offering an interactive and immersive learning experience. Based on the concept of constructivism, AR enables students to directly interact with learning objects, such as visualizations of Qur’anic verses and worship practices, fostering experiential learning and deeper understanding. The implementation of AR has proven to enhance interaction between teachers and students, making discussions more dynamic and learning more effective. However, the adoption of AR in PAI is not without obstacles. Major challenges include limited technological infrastructure in many schools, digital competency gaps among teachers and students, and the lack of IT support staff. In addition, there are difficulties in developing AR content that is both relevant and accurate in accordance with Islamic values, the high cost of implementation, and cultural or ethical resistance rooted in concerns about preserving spirituality. Integrating AR into an already dense curriculum and designing appropriate assessment methods also pose significant difficulties.To overcome these challenges, collaboration among educators is crucial in developing effective solutions that align with Islamic values. Therefore, AR holds the potential to be a transformative tool—not only enhancing the quality of Islamic Religious Education, but also shaping a generation that is both technologically literate and spiritually grounded with a deep understanding of Islam.